The Origin of the Plasma Cell Heterogeneity - Thierry Defrance (Frontiers Research Topics, 2015)
Plasma cells (PCs) are terminally differentiated B-cells producing large amounts of immunoglobulins (Ig). In humans, most of circulating Ig are produced by bone marrow plasma cells. PCs differentiate from activated naïve or memory B-cells usually activated by specific antigens. It is still controversial whether the regulation of PCs numbers and the "active" in vivo Ig diversity depend or not on non-specific reactivation of B-cells during infections. Depending on the stimulus (T-independent/T-dependent antigen, cytokines, partner cells) and B-cell types (naïve or memory, circulating or germinal center, lymph nodes or spleen, B1 or B2...), both the phenotype and isotype of PCs differ suggesting that PC diversity is either linked to B-cell diversity or to the type of stimulus or to both. Knowledge of the mechanisms supporting PC diversity has important consequences for the management of i) plasma cell neoplasia such as Multiple Myeloma and Waldenström's Macroglobulinemia, ii) vaccine protection against pathogens and iii) auto-immune diseases.